Diagnostic accuracy of increased C reactive protein levels in distal ureteric stone ejection prediction using a CT scan as the gold standard - Mudassar Saeed Pansota; Muhammad Shahzad Saleem; Asra Aleem; Burhan Barkat; Mumtaz Rasool (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVES: Numerous clinical urological diseases have been shown to benefit from CRP, such as the evaluation of renal injury in pyelonephritis, the determination of the severity of pediatric UTIs, and the prevention of voiding cystourethrography in cases of pediatric UTIs and vesicoureteral reflux. This study has been conducted to diagnose the accuracy of increased C reactive protein levels in distal ureteric stones.METHODOLOGY: In total, 184 individuals with single distal ureteric stones were included. Patients with severe hydronephrosis, multiple ureteral stones, impaired renal function, pregnancy, single kidney, endoscopic procedures, or prior ureteric surgery history or concomitant ureteric anomalies were excluded. Each patient had a blood sample sent to the hospital laboratory to evaluate the serum levels of CRP (c-reactive protein). For four weeks, the researcher checked in with each patient once a week. After that, each patient had computed tomography, and the data was evaluated to determine whether or not ureteric stones were present.RESULTS: The overall sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of elevated C reactive protein levels are 92.39%, 95.51%, 92.63%, and 94.02%, respectively, when using a CT scan as the gold standard to predict the ejection of a distal ureteric stone (p-value = 0.0001).CONCLUSION: This study found that elevated C reactive protein levels have a fairly high diagnostic accuracy in predicting the ejection of distal ureteric stones.